Crossing the divide: supporting students and families relocating from remote First Nations communities to urban centres - Guthrie, Anika (2020)
This research explores the experiences of First Nations students and families when they relocate from their homes in remote First Nations communities to an urban centre. The research considers student, family and school experiences during this relocation. The purpose of this study was to consider the role schools have in supporting families and students when they relocate from remote First Nations communities to an urban centre. It also explores what makes this transition “successful”, how that success is defined, what barriers families and students face, and how schools can be safe spaces for students during times of transition. The study uses Indigenous approaches to research in combination with more familiar qualitative methods. Data was collected through open-ended interviews and findings are presented in story form and participant voices and experiences. Findings provide recommendations for schools on what is needed to support families and students who relocate from remote First Nations communities to urban centres.